2019
DOI: 10.3791/60103
|View full text |Cite
|
Sign up to set email alerts
|

Production of <em>E. coli</em>-expressed Self-Assembling Protein Nanoparticles for Vaccines Requiring Trimeric Epitope Presentation

Abstract: Self-assembling protein nanoparticles (SAPNs) function as repetitive antigen displays and can be used to develop a wide range of vaccines for different infectious diseases. In this article we demonstrate a method to produce a SAPN core containing a six-helix bundle (SHB) assembly that is capable of presenting antigens in a trimeric conformation. We describe the expression of the SHB-SAPN in an E. coli system, as well as the necessary protein purification steps. We included an isopropanol wash step to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Since the use of the universal T-helper epitopes in vaccine design is a great help in increasing immunogenicity, and due to the effectiveness of the PADRE T-helper epitope in eliciting the immune response [ 21 , 22 , 44 47 ], this sequence was also used in PfGCS1-SAPN design to enhance the immunogenicity, that remains to be tested in future studies. Similar to previous studies [ 21 , 22 , 35 , 43 46 , 48 , 49 ], the designed amino acid sequence was confirmed to form the SAPN by assembling the monomers and surface exposure of antigenic determinants as confirmed by 3D structure prediction and assembly analysis. Besides, antigenic determinants are expressed on the surface of SAPNs formed by PfGCS1-SAPNs as verified by the ELISA.…”
Section: Discussionsupporting
confidence: 81%
“…Since the use of the universal T-helper epitopes in vaccine design is a great help in increasing immunogenicity, and due to the effectiveness of the PADRE T-helper epitope in eliciting the immune response [ 21 , 22 , 44 47 ], this sequence was also used in PfGCS1-SAPN design to enhance the immunogenicity, that remains to be tested in future studies. Similar to previous studies [ 21 , 22 , 35 , 43 46 , 48 , 49 ], the designed amino acid sequence was confirmed to form the SAPN by assembling the monomers and surface exposure of antigenic determinants as confirmed by 3D structure prediction and assembly analysis. Besides, antigenic determinants are expressed on the surface of SAPNs formed by PfGCS1-SAPNs as verified by the ELISA.…”
Section: Discussionsupporting
confidence: 81%
“…Specifically, the proximal pin allows splaying of the helical termini, which in turn leads to curved arrays that can close, whereas the distal pins give a more tightly constrained hairpin structure, consistent with building blocks required to make flat sheets. As noted earlier, others have developed similar self-assembling peptide and protein based nanoparticles [22][23][24][25][26][27][28][29][30] or sheets, [12][13][14][15][16][17][18] so what are the differences and advantages to our hairpin system? First, by including two points (loop and pin) that define the relative positions and rotational freedom of the two coiled-coil components, we are able to control the topology of the self-assembled structures by design in a single system to render closed nanoparticles or extended sheets.…”
Section: Conclusion and Future Outlookmentioning
confidence: 98%
“…11 Such structures are usually computationally driven towards forming closely packed 2D arrays [12][13][14][15][16][17][18] , tubes [19][20][21] or 3D icosahedral particles. [22][23][24][25][26][27][28][29][30] However, these beautifully ordered near crystalline assemblies may not be amenable to decoration with large cargos, or be very permeable to small molecules due to their close packed nature. Also, these designed arrays can require thermal annealing to assemble, 15,16 which may reduce or even destroy the activity of any appended functional proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAPN are agents known to provide intracellular delivery [186]. The production of SAPN at an industrial scale in GMP conditions for human vaccines, based on a system of expression in E. coli, has recently been described [187]. Curiously, in the studies of Karch et al, 2017 andLi et al, 2018, SAPN were linked to flagellin, an agonist of the non-endocytic TLR 5 located on the cell surface.…”
Section: Unknowns Behind Experimental Approaches To Np-tlr Agonists: ...mentioning
confidence: 99%